Peran Pendidikan Berbasis Higher Order Thinking Skills (Hots) Pada Tingkat Sekolah Menengah Pertama di Era Society 5.0 Sebagai Penentu Kemajuan Bangsa Indonesia - Ramadhan Prasetya Wibawa, Dinna Ririn Agustina (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2019)
At the time of the Industrial Revolution now the Indonesian government program for equity, has been re-launched society 5.0. Society 5.0 is an era initiated by the Japanese government with the concept of a human-centered society and technology-based. The current era of global competition requires the existence of quality learning to provide facilities for students in developing skills, skills and abilities as capital to face challenges in global life. Therefore it is necessary to apply the HOTS learning system (Higher Order Thinking Skills. Higher Order Thinking Skills (HOTS) is a process of thinking students in higher cognitive levels developed from various concepts and cognitive methods and taxonomy of learning such as problem solving methods, taxonomy bloom, and taxonomy of learning, teaching, and assessment.The main goal of high order thinking skills is how to improve students 'critical thinking skills at a higher level. The results are by applying HOTS learning (Higher Order Thinking Skills students' ability to think critically at school the middle class is faster in accepting various types of information, creative thinking in solving a problem using the knowledge they have and making decisions in complex situations.